Phân tích đa thức thành nhân tử
1) x^2 -4x + 4 - 16z2
2)3x-5+ 2x^2
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(1,=x\left(x^2-2x+1-y^2\right)=x\left[\left(x-1\right)^2-y^2\right]=x\left(x-y-1\right)\left(x+y-1\right)\\ 2,=\left(x+y\right)^3\\ 3,=\left(2y-z\right)\left(4x+7y\right)\\ 4,=\left(x+2\right)^2\\ 5,Sửa:x\left(x-2\right)-x+2=0\\ \Leftrightarrow\left(x-2\right)\left(x-1\right)=0\Leftrightarrow\left[{}\begin{matrix}x=1\\x=2\end{matrix}\right.\)
\(x^4-4x^3-2x^2-3x+2\)
\(\Leftrightarrow x^4+x^3-5x^3+x^2-5x^2+2x^2-5x+2x+2\)
\(\Leftrightarrow x^4+x^3+x^2-5x^3-5x^2-5x+2x^2+2x+2\)
\(\Leftrightarrow x^2\left(x^2+x+1\right)-5x\left(x^2+x+1\right)+2\left(x^2+x+1\right)\)
\(\Leftrightarrow\left(x^2-5x+2\right)\left(x^2+x+1\right)\)
Xin tick ạ !!!
1) 2x2 - 4x = 2x( x - 2 )
2) 3x - 6y = 3( x - 2y )
3) x2 - 3x = x( x - 3 )
4) 4x2 - 6x = 2x( x - 3 )
5) x3 - 4x = x( x2 - 4 ) = x( x - 2 )( x + 2 )
1) \(2x^2-4x=2x\left(x-2\right)\)
2) \(3x-6y=3\left(x-2y\right)\)
3) \(x^2-3x=x\left(x-3\right)\)
4) \(4x^2-6x=2x\left(2x-3\right)\)
5) \(x^3-4x=x\left(x-2\right)\left(x+2\right)\)
a) \(4x\left(a-b\right)+6xy\left(b-a\right)\)
\(=4x\left(a-b\right)-6xy\left(a-b\right)\)
\(=\left(4x-6xy\right)\left(a-b\right)\)
\(=2x\left(2-3y\right)\left(a-b\right)\)
a)x^2-(a+b)x+ab
= x^2 - ax - bx + ab
= (x^2 - ax) - (bx - ab)
= x(x-a) - b(x-a)
= (x-b)(x-a)
b)7x^3-3xyz-21x^2+9z
=
c)4x+4y-x^2(x+y)
= 4(x + y) - x^2(x+y)
= (4-x^2) (x+y)
= (2-x)(2+x)(x+y)
d) y^2+y-x^2+x
= (y^2 - x^2) + (x+y)
= (y-x)(y+x)+ (x+y)
= (y-x+1) (x+y)
e)4x^2-2x-y^2-y
= [(2x)^2 - y^2] - (2x +y)
= (2x-y)(2x+y) - (2x+y)
= (2x -y -1)(2x+y)
f)9x^2-25y^2-6x+10y
=
1: \(\dfrac{A}{B}=\dfrac{2x^4+4x^3-x^3-2x^2-2x^2-4x+x+2}{x+2}\)
\(=2x^3-x^2-2x+1\)
1: \(x^2-4x+4-16z^2\)
\(=\left(x^2-4x+4\right)-16z^2\)
\(=\left(x-2\right)^2-\left(4z\right)^2\)
\(=\left(x-2-4z\right)\left(x-2+4z\right)\)
2: \(3x-5+2x^2\)
\(=2x^2+5x-2x-5\)
\(=x\left(2x+5\right)-\left(2x+5\right)\)
=(2x+5)(x-1)
1. x^2-4x+4-16z^2=(x-2)2-(4z)2
=(x-2-4z)(x-2+4z)
2. 3x-5+2x^2=(2x2-2x)+(5x-5)
=2x(x-1)+5(x-1)
=(2x+5)(x-1)